Personnel governance of corporatized public services: Effects of executive resources and corporation forms on turnover - Ulf Papenfuß; Christian A. Schmidt (Public Administration, 2021)
Corporatization has potentials for public service provision but also induces far-reaching governance challenges. Appointing executives for public corporations is a powerful personnel governance mechanism for public authorities to manage public service provision and resource dependencies. However, the theoretical understanding of executive turnover is limited. Drawing on resource dependence theory and embedding publicness fit perspectives, Cox regressions for 491 executives of 275 German municipal corporations between 2006 and 2016 show that politicized executives, executives with higher pay, and internally hired executives have a longer tenure and a lower turnover likelihood. Furthermore, the findings reveal different governance rationalities between different corporation forms by showing a higher likelihood of executive turnover in not profit-making corporations than in profit-making corporations. This highlights the theoretical needs and potentials to conceptually differentiate between these two corporation forms in future research. Overall, this study enhances the theoretical understanding of executive turnover and provides important research perspectives. Die politischen Entscheidungen zur Auslagerung öffentlicher Aufgaben auf öffentliche Unternehmen haben hohe Potenziale für eine effektive und effiziente öffentliche Aufgabenerfüllung, führen aber zugleich zu weitreichenden Governance-Herausforderungen. Die Besetzung von Mitgliedern des Top-Managementorgans öffentlicher Unternehmen ist ein besonders relevanter personeller Governance-Mechanismus für öffentliche Anteilseignern zur Steuerung der öffentlicher Aufgabenerfüllung und Ressourcenabhängigkeiten. Basierend auf der Theorie der Ressourcenabhängigkeiten und Publicness-Fit-Perspektiven zeigt eine Cox-Analyse von 491 Top-Managementmitgliedern aus 275 deutschen kommunalen Unternehmen zwischen 2006 und 2016, dass politisierte, intern-nachbesetzte und Top-Managementmitglieder mit höherem Vergütungsniveau eine längere Amtszeit und eine geringere Wechsel-/Turnoverwahrscheinlichkeit aufweisen. Darüber hinaus zeigen die Ergebnisse unterschiedliche Governance-Rationalitäten zwischen verschiedenen Unternehmensformen. Demnach ist die Turnoverwahrscheinlichkeit von Top-Managementmitgliedern in nicht gewinnbringenden öffentlichen Unternehmen signifikant höher als in gewinnbringenden Unternehmen. Dies verdeutlicht den theoretischen Bedarf, diese beiden Unternehmensformen in der zukünftigen Forschung konzeptionell zu differenzieren. Insgesamt erweitert diese Studie das theoretische Verständnis zum Turnover von~Top-Managementmitgliedern und liefert wichtige Forschungsperspektiven.
Keywords: 340